Bioactive Compounds, Cosmeceutical And Nutraceutical Applications of Green Seaweed Species (Chlorophyta) - Muhammad Taher; Fatin Syazwani Ruslan; Deny Susanti; Normawaty Mohammad Noor; Nurul Iman Aminudin (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2021)
Seaweeds are valuable marine plants that have garnered much attention from the public due to their high bioactive, nutrients and minerals content. Seaweeds have been used in multiple applications, including in cosmeceutical, nutraceutical and pharmaceutical industries. Nevertheless, this review will focus on the bioactive compounds of Chlorophyta and their potential application in nutraceutical and cosmeceutical industries. Chlorophyta are believed to possess a significant amount of nutrients and minerals, sufficient to meet the daily requirements of nutrients and minerals in the human body.  Considering the nutritional aspect, deficiency in nutrients may lead to severe ailments, including heart disease, neurological disorder and cancer. The main compounds studied in this review are polysaccharides, proteins, amino acids, lipids, fatty acids, pigments, minerals, vitamins and secondary metabolites. Among all, polysaccharides are the most exploited compounds and used in many advanced applications in the nutraceutical and cosmeceutical industries. This review also offers insights into the beneficial biological properties of Chlorophyta, highlighting their potential in cosmeceutical and nutraceutical applications. Further research is required to highlight the Chlorophyta sp. aquaculture, its extraction method, and the most targeted bioactive compounds from the species. Therefore, the challenge is to increase public awareness of the promising application of this species in the nutraceutical and cosmeceutical  industries.